2012
DOI: 10.1139/f2012-098
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent habitat use and growth of an estuarine fish

Abstract: Density dependence can stabilize or destabilize population size through negative or positive feedback controls operating over different spatial and temporal scales. While many species have been shown to exhibit density dependence, the topic has received little attention in estuaries where environmental variability and larval supply are often considered to be the primary drivers of population dynamics. We used multiple long-term, fishery-independent data sets and a unique modeling approach to test the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, there are likely to be feedbacks between recruitment and growth operating at some scale that whist not detected here could also affect population productivity (e.g. maternal size and reproductive output Walsh et al ., ; or density‐dependence Bacheler et al ., ). Similar uncertainty will surround future productivity estimates of other estuarine fishes that respond to multiple environmental drivers and can only be resolved with more sophisticated stock assessment techniques based on comprehensive empirical data sets such as those presented here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, there are likely to be feedbacks between recruitment and growth operating at some scale that whist not detected here could also affect population productivity (e.g. maternal size and reproductive output Walsh et al ., ; or density‐dependence Bacheler et al ., ). Similar uncertainty will surround future productivity estimates of other estuarine fishes that respond to multiple environmental drivers and can only be resolved with more sophisticated stock assessment techniques based on comprehensive empirical data sets such as those presented here.…”
Section: Discussionmentioning
confidence: 97%
“…Carry‐over effects from variable environmental conditions experienced as a juvenile (e.g. inter‐annual variation in larval food availability) can manifest throughout an individual's life in terms their of growth (Whitten et al ., ), and year class strength can also have persistent effects on growth through density‐dependent competition for resources among same‐aged individuals (Amundsen et al ., ; Bacheler et al ., ). Our results suggest that persistent year class growth differences are primarily due to abiotic rather than density dependence effects as we failed to detect a relationship between growth and year class strength ( sensu Lobón‐Cerviá, ).…”
Section: Discussionmentioning
confidence: 99%
“…The release from density dependence is therefore not confined only to fish within the same cohort (e.g. Bacheler, Buckel, & Paramore, ; Whitten, Klaer, Tuck, & Day, ), but instead manifests across all age and size classes.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus noteworthy that density dependent factors were also considered responsible for the decline in growth of Micropogonias undalatus in the Neuse River Estuary (Eby et al, 2005). In addition, the use of fishery-independent data demonstrated that the growth of the 0þ and 1þ age classes of the red drum Sciaenops ocellatus were negatively related to the density of their own age classes (Bacheler et al, 2012). Furthermore, analysis of long-term records of size at age and biomass data for 16 fish populations revealed that the growth of individuals in nine of those populations was inversely related to density (Lorenzen and Enberg, 2002).…”
Section: Condition and Growthmentioning
confidence: 99%